A Conservative Approach to a Large Mycotic Pulmonary Pseudoaneurysm - Erin Torpey; Jenna Spears; Yousif Al-Saiegh; Mindi Roeser (Case Reports in Pulmonology)
Pulmonary mycotic pseudoaneurysm is a rare complication of bacteremia with high associated mortality. We present a case of a large proximal pulmonary artery pseudoaneurysm as a result of methicillin-sensitive Staphylococcus aureus bacteremia, originating from a tunneled dialysis catheter infection. This case was ultimately managed conservatively with surveillance imaging and a prolonged intravenous antibiotic course, rather than with surgical or interventional management. To our knowledge, this is the first reported case of a mycotic pulmonary pseudoaneurysm due to septic embolization of an infected superior vena cava thrombus.